Patriarcalismo e jeitinho brasileiro: algumas manifestações na contemporaneidade - Oliveira, Fátima Modesto de (2008)
This dissertation aims at recovering some characteristics of the patriarchal family described by Gilberto Freyre and dialogues that Sérgio Buarque de Holanda and Roberto Da Matta have developed with these categories. One tries to point out as certain forms of sociability perceived by those authors which can be found today in terms of the social imaginary, through approaches of the early years cinema of the twenty-first century